PENGARUH KADAR AIR DAN SUHU TANAH TERHADAP PENYEBARAN RAYAP TANAH - Agus Ismanto; Ginuk Sumarni (Jurnal Penelitian Hasil Hutan, 1992)
The  result  of  a  study  on  the  effect  of soil moisture  content and  temperature  on subterranean  termite  distribution is presented   in this paper.The study  shows   that   soil  moisture   content   and   temperature  has significant   effect   on  subterranean  termite distribution. Four  subterronean   termites   namely  Microtermes  incertoides,  M.  insperatus,  Macrotermes  gilvus and Coptotermes  curvignathus  were  identified   at  the  first  location   (soil  moisture  content  = 21. 71 %,  soil  temperature   = 25. 7oc).   Whereas  at  the  second   location   (soil  moisture content =  8.36%,   soil  temperature  =  27.5°C)   two  species  only were  identified   namely  M. incertoides and  M.  insperatus.